Elevations in serum anti-flagellin and anti-LPS Igs are related to growth faltering in young Tanzanian children. Issue 6 (27th April 2016) - McDonald, Christine M; Manji, Karim P; Gosselin, Kerri; Tran, Hao; Liu, Enju; Kisenge, Rodrick; Aboud, Said; Fawzi, Wafaie W; Gewirtz, Andrew T; Duggan, Christopher P
ABSTRACT: Background: Antibodies to LPS and flagellin have been described as indirect measures of increased gastrointestinal permeability and may be markers of environmental enteric dysfunction (EED), which is a condition associated with poor child growth. Objective: We assessed whether LPS- and flagellin-specific immunoglobulin (Ig) concentrations were associated with poor growth in young Tanzanian children at risk of EED. Design: Blood samples were obtained from 590 children at 6 wk, 6 mo, and 12 mo of age. Serum LPS- and flagellin-specific Ig concentrations (IgA and IgG) were measured with the use of an ELISA. Growth was measured on a monthly basis for 18 mo. Results: Anti-LPS and anti-flagellin IgA and IgG concentrations increased over the first year of life and were higher than concentrations (measured at 9 mo of age) in healthy controls. Children with anti-flagellin IgA, anti-LPS IgA, anti-flagellin IgG, and anti-LPS IgG concentrations in the highest quartile at 6 wk of age were 2.02 (95% CI: 1.11, 3.67), 1.84 (95% CI: 1.03, 3.27), 1.94 (95% CI: 1.04, 3.62), and 2.31 (95% CI: 1.25, 4.27) times, respectively, more likely to become underweight (weight-for-age z score <−2) after adjustment for covariates ( P -trend < 0.05) than were children with Ig concentrations in the lowest quartile. Children with increased concentrations of anti-flagellin IgA were also more likely to become wasted; however, there was no association between any of the markers and subsequent stunting. Conclusion: Serologic measures of increased intestinal permeability to bacterial components are associated with subsequent poor growth and could help identify children who may benefit most from preventive interventions. This trial was registered at clinicaltrials.gov as NCT00421668.